PERANCANGAN ULANG INTERIOR RUANG KERJA INSTALASI REKAM MEDIS DI RUMAH SAKIT UMUM DAERAH KOTA YOGYAKARTA - , SEKAR MUGEN BINHARTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Ergonomics is defined as the study of human aspects in the work environment are reviewed in anatomy, physiology, psychology, engineering, management and design / drafting. Storage racks in the hospital medical record file Yogyakarta is almost full so requires additional shelves and wider space. Filing space which will lead to expanded medical records management space becoming increasingly narrow. Location of medical records management space is right next door to the room because it filing. Yogyakarta Hospital management will move medical records management space to space and Information Technology Installation business will extend the filing room. Objective. The objective of this scheme is to redesign the interior workspace medical records so convenient and efficient to improve the performance of medical records with attention to the needs of the medical records officer but still pay attention to ergonomic aspects. Methods: The method used in this design is space planning methods Mark Karlen. This method consists of two phases: pre-design and design phase. Theme: The theme of this scheme is to re-design or redesign the interior of the workspace of existing medical records at the General Hospital of the city of Yogyakarta by taking into account the comfort and security of medical records personnel and the needs and ergonomic aspects of space planning using Mark Karlen. Results: The design obtained is three draft design space and filing medical records space above. A filing room design and space management or medical records over the space obtained is a result of the recommendation of the respondents. The design results are less accommodate the needs of users due to the narrow room. The results of the design chosen for managing medical records space is the result of a modification of the design alternatives 1 and filing a design space that can accommodate 24 racks of wood and a set of roll o'pack. .